Using analytics-driven automation to target the biggest vulnerabilities. Issue 2 (February 2019) - Keef, Sean
Abstract : In 2017, the National Vulnerability Database published 14, 000 new Common Vulnerabilities and Exposures (CVEs) – more than double the amount published the previous year. 1 According to mid-year analysis, 2018 is on track to surpass even that record-shattering figure. 2 Organisations using traditional methods to deal with their own massive volumes of vulnerability occurrences will only see problems compound. To deal with vulnerabilities on a scale never seen before, organisations will have to shift to a better, threat-centric approach to vulnerability management. To deal with vulnerabilities on a scale never seen before, organisations need to shift to a better, threat-centric approach to vulnerability management. Threat-centric vulnerability management focuses heavily on intelligently prioritising vulnerabilities by risk rather than severity, analysing vulnerabilities in the context of exposure within the network, potential business impacts and the activity of exploits in the wild. And to do this effectively, especially with the current security skills gap, means automating, argues Sean Keef of Skybox Security.